Implications of the IQ-CSRC Prospective Study: Time to Revise ICH E14 - Darpo, Borje; Garnett, Christine; Keirns, James; Stockbridge, Norman (DRUG SAFETY, 2015)
Exposure-response (ER) analysis has evolved as an important tool to evaluate the effect of a drug on cardiac repolarization, as reflected in the QTc interval. It has been suggested that careful electrocardiogram (ECG) evaluation in ‘first-in-human’ studies using ER analysis could replace or serve as an alternative to the E14 ‘thorough QT’ study. This commentary shares and discusses the results of a recently conducted study with the objective to evaluate this approach. Six drugs with a well-characterized QT effect, five of which are known QT prolongers, were evaluated in a study design similar to a conventional single-ascending-dose study. Each drug was given to nine healthy subjects (six for placebo) in two dose levels, which for the positive drugs (ondansetron, quinine, dolasetron, moxifloxacin, and dofetilide) were chosen with the intent to cause 10–12 ms and 15–20 ms QTc prolongation. Replicate 12-lead ECGs were extracted from continuous recordings pre-dose and serially after dosing and paired with drug concentration determinations. The ER criteria for the identification of a QT effect, a statistically significant positive ER slope and an effect above 10 ms, were met with all five positive drugs, and an effect exceeding 10 ms could be excluded at the supratherapeutic dose of the negative drug, levocetirizine. The study results thereby provided evidence to support that careful QT assessment in early phase clinical studies can be used as an alternative to the thorough QT study. Clinical and regulatory implications, as well as limitations of this approach, are discussed in the commentary.